DiGeorge syndrome critical region gene 2 (DGCR2), a schizophrenia risk gene, regulates dendritic spine development through cell adhesion - Dongyan Ren; Bin Luo; Peng Chen; Lulu Yu; Mingtao Xiong; Zhiqiang Fu; Tian Zhou; Wen-Bing Chen; Erkang Fei (Cell & Bioscience, 2023)
Abstract Background Dendritic spines are the sites of excitatory synapses on pyramidal neurons, and their development is crucial for neural circuits and brain functions. The spine shape, size, or number alterations are associated with neurological disorders, including schizophrenia. DiGeorge syndrome critical region gene 2 (DGCR2) is one of the deleted genes within the 22q11.2 deletion syndrome (22q11DS), which is a high risk for developing schizophrenia. DGCR2 expression was reduced in schizophrenics. However, the pathophysiological mechanism of DGCR2 in schizophrenia or 22q11DS is still unclear. Results Here, we report that DGCR2 expression was increased during the neurodevelopmental period and enriched in the postsynaptic densities (PSDs). DGCR2-deficient hippocampal neurons formed fewer spines. In agreement, glutamatergic transmission and synaptic plasticity were decreased in the hippocampus of DGCR2-deficient mice. Further molecular studies showed that the extracellular domain (ECD) of DGCR2 is responsible for its transcellular interaction with cell adhesion molecule Neurexin1 (NRXN1) and spine development. Consequently, abnormal behaviors, like anxiety, were observed in DGCR2-deficient mice. Conclusions These observations indicate that DGCR2 is a novel cell adhesion molecule required for spine development and synaptic plasticity, and its deficiency induces abnormal behaviors in mice. This study provides a potential pathophysiological mechanism of DGCR2 in 22q11DS and related mental disorders.